Analisis Kedisiplinan Pegawai Sebelum dan Sesudah Melalui Sistem Informasi Absensi Presensi (SIAP) Untuk Meningkatkan Kinerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Karawang - Fitria Nurfirdayani; Sari Marliani; July Yuliawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to analyze employee discipline before and after through the attendance attendance information system (SIAP) on employee performance at the Karawang Regency Personnel and Human Resources Development Agency. This research was conducted at BKPSDM Karawang Regency which is located at Jl. A, Yani No.1, Nagasari West Karawang, Karawang Regency. The method used is descriptive qualitative. Participation of informants as many as 4 employees. Analysis techniques used observation, interviews and documentation using Descriptive Qualitative. The results of the study were 1) discipline before using SIAP there was still employee discipline that decreased. 2) discipline after using SIAP there is improved employee discipline. 3) Performance before using SIAP there are still employees with low performance targets. 4) Performance after using SIAP has improved, although there are still some employees with low performance targets.